Hubungan Memorable Culinary Tourism Experiences dan Minat Berkunjung Kembali Wisatawan di Warung Kopi Klotok Yogyakarta - Rahayu, Intan Widyaningrum Puji; Yusuf, Mohamad (Jurnal Master Pariwisata (JUMPA); Volume 07, Nomor 02, Januari 2021DO - 10.24843/JUMPA.2021.v07.i02.p09, 2021)
Several studies have confirmed that experience is the main goal of the tourism industry and as a significant impression for the tourist. However, there has been few studies investigating the memorable tourism experience (MTE) concept in culinary tourism, and more specifically in traditional culinary tourism, which is called the Memorable Culinary Tourism Experience (MCTE). This research aims to investigate the application of MCTE in traditional culinary tourism of Warung Kopi Klotok, and to discover the correlation between MCTE and the tourist revisit intention. Five aspects of MCTE were applied, namely local culture, decore, service quality, social interaction, and novelty. There were 267 respondents involved in this research coming from various areas in Indonesia. Two steps of data analysis were performed. We conducted a descriptive analysis to investigate level of agreement of tourist toward MTCE variables. In addition, we conducted a correlation analysis to investigate the extend of which MCTE variables are correlated with tourist revisit intention. This study shows that local culture has the highest level of agreement among the tourists, followed by social interaction, décor, service quality and novelty. Social interaction has the higest and positive correlation with tourist revisit intention, followed by décor. Interestingly, local culture has the second lowest and positive correlation with revisit intention after novelty variable. Keywords: culinary tourism, memorable culinary tourism experience, revisit intention, Warung Kopi Klotok Pakem, Yogyakarta